The King James Bible across Borders and Centuries - Duran, Angelica (Book collections on Project MUSE., 2014)
"Twelve essays by scholars from a variety of academic disciplines examine the King James Version of the Bible both as world literature and as an important force in social, geographical, and linguistic cultures, demonstrating its influence from the Protestant Reformation to the present day"--